The Influence of Trampoline Dance on Physical and Mental Health - Kodrad Budiyono; Dwi Gunadi; Mahendri Bakhtiar; Adimas Alfin; Mahendri Mahendri (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
Trampoline Dance, a dynamic aerobic exercise conducted on a trampoline, integrates physical training with creativity, providing cardiovascular and mental health advantages. This study examines the impact of Trampoline Dance on physical and mental well-being through a quasi-experimental design including 50 students from the PKO program at Tunas Pembangunan University. The Wilcoxon Signed Ranks test was employed for data analysis due to the ordinal characteristics of the data, which made parametric tests inappropriate. The findings indicated substantial enhancements in both physical and mental health indicators among individuals in the experimental group, who practiced frequent trampoline dancing, in contrast to the control group. Participants demonstrated improved cardiovascular endurance, muscular strength, balance, and mental health outcomes, including less anxiety and heightened self-confidence. The findings indicate that Trampoline Dance is an efficacious and pleasurable fitness intervention that enhances both physical and psychological well-being, rendering it appropriate for integration into contemporary fitness regimens.